Prática construtiva como práxis educativa: experiências curriculares de ensino e aprendizagem a partir da noção de canteiro - Silva, Luciana Romão da (2024)
The research is based on an educational experience that took place at the Space of Technologies and Arts (ETA) of Sesc-SP, Itaquera Operational Unit, in the year 2022 – the ETA Experimental Job Site – to bring to Curriculum studies a little-known perspective on production and sharing of knowledge, teaching and learning, which originates in a field apparently unrelated to such discussions, architecture. Based on the philosophical concept of praxis, it revisits the notion of construction job site in three possible meanings of the term: as a space of production in civil construction; as a space and educational program in higher education of architecture and as epistemological arrangement of knowledge and practices capable of guiding educational actions. To this end, it brings Karel Kosik and Paulo Freire as main reference authors to support the concept of praxis; Sérgio Ferro and Rodrigo Lefèvre to present critical theory in architecture; Reginaldo Ronconi to understand the Experimental Job Sites; Iván Illich and, again, Paulo Freire, to think about the confluences between architecture and education; Ivor Goodson to reflect on curriculum. It recovers the historical trajectory that, since the 1960s, has led architecture and education along parallel paths – does it work for the people or work with the people? –, identifying concepts, theoretical perspectives and practical propositions that guide critical theory in both fields. Finally, it presents the Space of Technologies and Arts of Sesc Itaquera and describes the educational experience of the ETA Experimental Job Site (2022), inquiring about its mistakes and outlining, based on them, other paths and curricular understandings for new educational practices